Stability Analysis in Individuals with Complete and Incomplete Spinal cord Injury: Linear Versus Non-Linear Methods - Hamidreza Kargar; Vahid Zolaktaf (Shiraz University of Medical Sciences, 2017)
Background: Individuals with spinal cord injury (SCI) lose their abilities to stand. The effectiveness of compensating strategies such as the use of various orthosis is studied by stability analysis. These kind of analyses are usually studied by linear method. In this study, the standing stability of complete and incomplete SCI individuals is evaluated by linear versus non-linear methods. Methods: Study groups consisted of 10 normal, 5 incomplete and 5 complete SCI individuals. SCI participants stood with crutch and/or orthosis on a Kistler force plate. The excursions of center of pressure (COP), velocity of COP, correlation dimension, and approximate entropy in the anteroposterior and mediolateral planes were calculated in this study. Statistical analysis was done by one-way ANOVA and Post-hoc calculations by Tukey HSD. Results: Linear method revealed that the difference in "the mediolateral COP sway" and "anteroposterior COP velocity" was insignificant among the groups, whilst the difference in "anteroposterior COP sway", "mediolateral COP velocity" and "total velocity" was significant. In contrast, non-linear method revealed that the difference in "mediolateral embedding diversion", "anteroposterior embedding diversion", "mediolateral correlation dimension" and "anteroposterior ApEn" was insignificant among the groups, whilst the difference in "anteroposterior correlation dimension" and "mediolateral ApEn" was significant. Conclusion: Based on linear method, the stability of SCI subjects seems to be like normal subjects. However, non-linear analysis revealed that although SCI patients knew how to put their body in a good posture to have a stable position, they had no abilities to control their posture.